MANAJEMEN PENDIDIKAN KARAKTER PESERTA DIDIK MELALUI KEGIATAN EKSTRAKURIKULER PRAMUKA - Darmiati Darmiati (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2019)
Management is the process of utilizing all resources in order to achieve the goals set. The management process includes: planning, organizing, implementation, and supervision. the substance of management that exist in educational institutions and become an important focus in the world of education are learners. the purpose of this study is to explain the character education management of learners through extracurricular activities scouting in MTs Negeri 2 Ogan Ilir. This research uses qualitative approach with descriptive method. data collection methods used in the form of observation, interviews, and documentation. MTs Negeri 2 Ogan Ilir, character education in all areas of activity including extracurricular activities scout.